2003
DOI: 10.1177/152660280301000217
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Carotid Artery Flow Velocities after Stent Implantation: A Fluid Dynamics Study with Laser Doppler Anemometry

Abstract: Anatomically correct positioning of appropriately sized stents does not lead to relevant flow disturbances in the ICA. In the ECA, depending on the position, size, and interstices of the stent, the physiological flow was considerably disturbed when any part of the stent covered the inflow of the vessel. Disturbances were seen when the stent was positioned into the bulb. For clinical application, stent location and size must be carefully determined so that the stent covers the bifurcation completely or is in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…A larger risk area is found in case of treatment‐C as compared with treatment‐O. This can be ascribed to the higher number of struts and the smaller cell size of the closed‐cell design stent and matches with the observation of Greil et al who, based on the analysis of a silicon carotid artery model using Laser Doppler Anemometry, reported that larger cell stents may lower the flow disturbance in the bifurcation. Besides the primary role played by the stent cell size, vessel straightening may also contribute.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A larger risk area is found in case of treatment‐C as compared with treatment‐O. This can be ascribed to the higher number of struts and the smaller cell size of the closed‐cell design stent and matches with the observation of Greil et al who, based on the analysis of a silicon carotid artery model using Laser Doppler Anemometry, reported that larger cell stents may lower the flow disturbance in the bifurcation. Besides the primary role played by the stent cell size, vessel straightening may also contribute.…”
Section: Discussionsupporting
confidence: 82%
“…A straightened vessel loses 3D geometrical features such as bending and twisting and, consequently, reduces 3D fluid dynamics features such as helical flow in the bulk, which is supposed to improve the arterial hemodynamics . As an extreme case, vessel straightening may be responsible for stenosis formation distal to the stent after the procedure .…”
Section: Discussionmentioning
confidence: 99%
“…Stent migration is one of the major factors affecting the clinical efficiency of carotid stenosis stent angioplasty, which is more common when using the whole-weaving type of stent (Greil et al, 2003). Reports have indicated that the laser-carved stent only needed the first 2 to 3 stages for releasing, after which the stent could firmly anchor to the walls of blood vessels, and generally did not show situations of moving forward or backward (Alvarez et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…10 Furthermore, in vitro models have demonstrated abnormal ECA flow dynamics when the stent is extended across the ECA orifice. 11 Thus, we sought to determine whether patients undergoing CAS had any change in ECA patency and any resultant symptoms.…”
Section: ¤ ¤mentioning
confidence: 99%